Analysis of Payback Period, Net Present Value and Internal Rate of Return on hotel business in Kepulauan Seribu - Muhammad Nasim Harahap (UNSIKA (Universitas Singaperbangsa Karawang), 2020)
This analysis was conducted to determine the feasibility of investing in a tourism area in the Thousand Islands, with the aim of whether the investment carried out was feasible to continue or not feasible to continue. In this analysis, the methods of Payback Period (PP), Net Present Value (NPV) and Internal Rate of Return (IRR) are used. The research method used in this study uses primary and secondary data. Based on the results of the Payback Period (PP) analysis obtained within 5 years, the Net Present Value (NPV) value is Rp. 480,200,278., while the Internal Rate of Return (IRR) is 17% greater than the interest rate of 15% (17%> 15%). Thus, these results can be concluded that investment in the hotel business in the Kepulauan Seribu is feasible.